1948
DOI: 10.1002/bjs.18003614105
|View full text |Cite
|
Sign up to set email alerts
|

Tantalum in the repair of traumatic skull defects

Abstract: scaphoid, and capitate, which has the largest. The metacarpals and the phalanges of the second to fifth digits are broadened and have hardly any cortex. There are cysts up to I cm. in diameter in the heads of the metacarpals, the bases and heads of all the phalanges, and the base of the terminal phalanx of the thumb (Fig. 49). FIG. 49.-Showing right hand with cysts in the scaphoid and capitate and affection of the 2nd to 5th metacarpals and all the phalanges. Left hand for comparison. COMMENTA typical case of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1949
1949
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…In rhe cases of Lewin er al. (14) the rate of infection was 9 %. The occurrence of pneumatocele secondary to defects of the frontal sinus is weil known .…”
Section: Diseussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In rhe cases of Lewin er al. (14) the rate of infection was 9 %. The occurrence of pneumatocele secondary to defects of the frontal sinus is weil known .…”
Section: Diseussionmentioning
confidence: 98%
“…0 1 rhe 52 plates removed, 26 (50%) had been insert ed in the front al area of the skull, and in 18 of these 26 cases, or 35 % of the tota l, the cran ial defecr involved the fro ntal sinus. Lewin et al (14) reported 130 rantalum cranioplasties in 128 parienrs in who m infecrion occurr ed in 9 cases, of which 4 were tr eated conservatively wirho ur removal of the tant alum plate. The infection occurred between seven weeks and two years and seven months after cranioplasry.…”
Section: Diseussionmentioning
confidence: 99%
“…The authors sutured adjacent pericranium or periosteum to perforations made in the plate. 37 In some cases, they covered the plate with an additional layer of fascia lata that was sutured to surrounding pericranium. They noted that this method was often insufficient for frontal cranioplasties, likely due to the added effect of gravity.…”
Section: Implant Fixation Techniquementioning
confidence: 99%
“…37,42,44,56,75 Two studies reported on return to duty outcomes after tantalum cranioplasty. 44,75 The larger of the two studies (79 patients) reported that 46% of soldiers returned to duty and 54% were discharged from the military, most commonly due to neurological deficits or either clinical seizures or the presence of an epileptogenic focus on electroencephalography (EEG).…”
Section: Clinical Outcome and Complicationsmentioning
confidence: 99%
“…Tantalum was used after -the 1939-45 war (Woodhall and Spurling, 1947). It was shaped by a die/ counter die swaging technique or by hanmnering into a counter die (Lewin et al, 1948). Lewin and Gibson (1956) used tantalum to repair some of -the skull defeots in British soldiers injured in Korea.…”
Section: Introductionmentioning
confidence: 99%